2013
DOI: 10.1515/mammalia-2012-0075
|View full text |Cite
|
Sign up to set email alerts
|

Differences in population parameters of Rattus norvegicus in urban and rural habitats of central Argentina

Abstract: Life history characteristics are influenced by both biotic and abiotic factors of the environment. The aim of this study was to compare the life history strategies of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…rattus was absent [ 62 ] and with reports from other countries where R . norvegicus is distributed in all habitats including rural areas [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…rattus was absent [ 62 ] and with reports from other countries where R . norvegicus is distributed in all habitats including rural areas [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trap success (TS) was used to estimate the relative rodent abundance as follows: number of rats trapped − 100/(number of traps − number of nights) [41]. The non-parametric Mann–Whitney [ U -test was used to compare the TS between rodent species.…”
Section: Methodsmentioning
confidence: 99%
“…Although the Norway rat has a worldwide distribution, most studies on rat populations have been focused in temperate areas [ 10 15 ]. These studies have shown that reproductive parameters vary significantly among seasons or habitats (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal differences are influenced by both biotic and abiotic factors of the environment (e.g. photoperiod, food supply, and weather) that interact to regulate their growth rate and reproductive development [ 15 ]. Additionally, morphometric differences between temperate and tropical rat populations, consistent with Bergmann’s rule, add a further complication to direct generalizations of rats sampled from different latitudes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%